2016
DOI: 10.1016/j.theriogenology.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Thermoprotective effect of insulin-like growth factor 1 on in vitro matured bovine oocyte exposed to heat shock

Abstract: a b s t r a c tThe role of insulin-like growth factor 1 (IGF1) on cellular function and developmental capacity of heat-shocked oocytes has not been completely understood. Therefore, the objective of this study was to determine the effect of IGF1 on apoptosis, mitochondrial activity, cytoskeletal changes, nuclear maturation, and developmental competence of bovine oocytes exposed to heat shock. Cumulus-oocyte complexes were submitted to control (38.5 C for 22 hours) and heat shock (41 C for 14 hours followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 72 publications
1
24
0
1
Order By: Relevance
“…At least part of the deleterious effects of heat shock on oocyte function is mediated by cellular and molecular damage to the oocyte. For example, heat shock reduced mitochondrial activity 36 , caused cytoskeleton disorganization 35 , 36 , protein denaturation, mRNA degradation as well as apoptosis 32 , 57 59 . In the present study, inhibition of autophagy prone the oocyte more susceptible to heat shock reducing the ability to cleave and reach the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least part of the deleterious effects of heat shock on oocyte function is mediated by cellular and molecular damage to the oocyte. For example, heat shock reduced mitochondrial activity 36 , caused cytoskeleton disorganization 35 , 36 , protein denaturation, mRNA degradation as well as apoptosis 32 , 57 59 . In the present study, inhibition of autophagy prone the oocyte more susceptible to heat shock reducing the ability to cleave and reach the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment was arranged in a 2 × 2 factorial design to determine the effect of temperature (38.5 or 41 °C) and autophagy inhibitor (0 or 10 mM 3MA) during IVM on autophagy activity by measuring LC3 protein level (autophagy marker). COCs were distributed on the following experimental groups: Control (38.5 °C for 22 h) and Heat Shock (41 °C for 16 h followed by 38.5 °C for 6 h 36 , 37 ), in the presence of 0 or 10 mM 3MA during IVM 38 . After IVM, COCs were denuded so that denuded oocytes and respective cumulus cells were processed for western blotting analysis to determine autophagy activity by LC3-I and LC3-II level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical F‐actin was evaluated as described early (Rodrigues et al, 2016). Briefly, ImageJ version 1.43 was used to analyze the oocyte's digital images.…”
Section: Methodsmentioning
confidence: 99%
“…In pigs, although IGF-I has been reported to promote the synthesis of hyaluronic acid and the expansion of cumulus cells (Nemcova et al, 2007), its role in IVM remains unclear and has yield inconsistent results. Nevertheless, several studies reported that the addition of IGF-I during in vitro maturation and culture decreases apoptosis in bovine oocytes (Wasielak and Bogacki, 2007; Rodrigues et al, 2016; Ascari et al, 2017) and in porcine blastocysts (Wasielak et al, 2013). Wasielak et al (2013) also demonstrated that adding IGF-1 at a concentration of 100 ng/ml into maturation medium increases the BCL2L1:BAX transcript ratio in pig blastocysts, and the increased expression of anti-apoptotic genes, such as BCL2 , and a decreased expression of apoptotic-related genes, such as BAX , indicates higher blastocyst quality (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%